The improvement of methodological approaches in the field of metrological provision of technology leakage control at hazardous production facilities - P. S. Sumkin; U. N. Moiseev; I. I. Usachyov; A. E. Aref'ev (Стандартные образцы)
In this article the analysis of metrological assurance of control technologies integrity subject to the rules of safety at hazardous production facilities. Deals with the scientific and methodological aspects of the evaluation of threshold sensitivity of control systems integrity using controlled leaks, containing in its composition of standard samples for reproduction of units of volumetric and mass flow of gas, which expands the scope of their applicability.